When Do Interlocks Matter?: Alternate Sources of Information and Interlock Influence - Haunschild, Pamela R.; Beckman, Christine M. (Administrative Science Quarterly, 1998)
Pamela R. Haunschild, Christine M. Beckman, When Do Interlocks Matter?: Alternate Sources of Information and Interlock Influence, Administrative Science Quarterly, Vol. 43, No. 4 (Dec., 1998), pp. 815-844